Evaluation of AZD1446 as a Therapeutic in DYT1 Dystonia - Zimmerman, Chelsea N.; Eskow Jaunarajs, Karen L.; Meringolo, Maria; Rizzo, Francesca R.; Santoro, Massimo; Standaert, David G.; Pisani, Antonio (Frontiers in Systems Neuroscience, 2017)
DYT1 dystonia is an early-onset, hyperkinetic movement disorder caused by a deletion in the gene TOR1A, which encodes the protein torsinA. Several lines of evidence show that in animal models of DTY1 dystonia, there is impaired basal dopamine (DA) release and enhanced acetylcholine tone. Clinically, anticholinergic drugs are the most effective pharmacological treatment for DYT1 dystonia, but the currently used agents are non-selective muscarinic antagonists and associated with side effects. We used a DYT1 ΔGAG knock-in mouse model (DYT1 KI) to investigate whether nicotine and/or a non-desensitizing nicotinic agonist, AZD1446, would increase DA output in DYT1 dystonia. Using in vivo microdialysis, we found that DYT1 KI mice showed significantly increased DA output and greater sensitivity to nicotine compared to WT littermate controls. In contrast, neither systemic injection (0.25 mg/kg - 0.75 mg/kg) or intrastriatal infusion (30 µM - 1 mM) of AZD1446 had a significant effect on DA efflux in WT or DYT1 KI mice. In vitro, we found that AZD1446 had no effect on the membrane properties of striatal spiny projection neurons (SPNs) and did not alter the spontaneous firing of ChI interneurons in either WT or DYT1 KI mice. We did observe that the firing frequency of dopaminergic neurons was significantly increased by AZD1446 (10 µM), an effect blocked by dihydro-beta-erythroidine (DHβE 3 µM), but the effect was similar in WT and DYT1 KI mice. Our results support the view that DYT1 models are associated with abnormal striatal cholinergic transmission, and that the DYT1 KI animals have enhanced sensitivity to nicotine. We found little effect of AZD1446 in this model, suggesting that other approaches to nicotinic modulation should be explored.